Practicing Gnosis : ritual, magic, theurgy, and liturgy in Nag Hammadi, Manichaean and other ancient literature : essays in honor of Birger A. Pearson - De Conick, April D.; Shaw, Gregory, 1951-; Turner, John Douglas.; Pearson, Birger A. 1934- (Nag Hammadi and Manichaean Studies, 2013)
Ritual, magic, liturgy, and theurgy were central features of Gnosticism, and yet Gnostic practices remain understudied. This anthology is meant to fill in this gap and address more fully what the ancient Gnostics were doing. While previously we have studied the Gnostics as intellectuals in pursuit of metaphysical knowledge, the essays in this book attempt to understand the Gnostics as ecstatics striving after religious experience, as prophets seeking revelation, as mystics questing after the ultimate God, as healers attempting to care for the sick and diseased. These essays demonstrate that the Gnostics were not necessarily trendy intellectuals seeking epistomological certainities. They were after religious experiences that relied on practices. The book is organized comparatively in a history-of-religions approach with sections devoted to Initiatory, Recurrent, Therapeutic, Ecstatic, and Philosophic Practices. This book celebrates the brilliant career of Birger A. Pearson.